Evidence for protein leverage in a general population sample of children and adolescents - Saner Christoph; Senior Alistair M.; Zhang Hanyue; Eloranta Aino-Maija; Magnussen Costan G.; Sabin Matthew A.; Juonala Markus; Janner Marco; Burgner David P.; Schwab Ursula; Haapala Eero A.; Heitmann Berit L.; et al. (SPRINGERNATURE, 2025)
Background/Objectives
The strong regulation of protein intake can lead to overconsumption of total energy on diets with a low proportion of energy from protein, a process referred to as protein leverage. The protein leverage hypothesis posits that protein leverage explains variation in energy intake and potentially obesity in ecological settings. Here, we tested for protein leverage and the protein leverage hypothesis in children and adolescents.
Subjects/Methods
A population sample of children, mean (SD) age 7.6 (0.4) years (n = 422), followed up at age 9.8 (0.4) years (n = 387) and at age 15.8 (0.4) years (n = 229), participating for the Physical Activity and Nutrition in Children (PANIC) study. Exposures: 4-day food records-related proportional energy intake of proteins, fats, and carbohydrates. Outcomes: energy intake, body mass index (BMI) z-score and dual-energy X-ray absorptiometry-related energy expenditure.
Results
Proportional energy intake of proteins was inversely associated with energy intake following power functions at all 3 ages (mean [95%CI] strength of leverage of L = -0.36 [-0.47 to -0.25]; L = -0.26 [-0.37 to -0.15]; L = -0.25 [-0.38 to -0.13]; all P < 0.001). Mixture analysis indicated that variance in energy intake was associated primarily with the proportional intake of energy from proteins, not with either fats or carbohydrates. At all 3 ages, energy intake was not associated with BMI z-score but positively associated with energy expenditure (all P < 0.001).
Conclusions
This study provides evidence consistent with protein leverage in a population sample of children and adolescents. Increased energy intake on diets with lower protein content was counterbalanced by increased energy expenditure and therefore did not translate into increased adiposity.